Glacier disasters in the French Alps - Valla, Francois; Reynaud, Louis; Buisson, Anne; Guirado, Florence (Journal of Nepal Geological Society, 2000)
In France, an extensive inventory of glacier-induced disasters was started by LGGE-CNRS and CEMAGREF-ETNA in 1998 for the French Alps. Inquiries, archive s, and field visits made it possible to register more than a hundred events during the past two centuries. Results are synthesised in specific cards for each glacier with its geographic description (location, parameters, picture) and a short summary of the event. The French Alps are divided into four massifs and the example from the Mont Blanc Range is presented in this paper. Three main types of hazard associated with the glaciers are: outburst of glacier lakes, fall of ice (repetitive serac falls or glacier tongue ruptures), and draining of internal water pockets. Temporal distributions are analysed for each hazard based on the past French and Swiss glacier disasters. It is also proposed to create a "French glacier observatory" as well as to seek an extensive co-operation at the scale of the whole Alps.